P001 Safety, tolerability, and efficacy of 1 month of atomoxetine plus oxybutynin in obstructive sleep apnoea. (7th October 2021) - Aishah, A; Loffler, K; Tonson, B; Mukherjee, S; Adams, R; Altree, T; Ainge-Allen, H; Yee, B; Grunstein, R; Taranto-Montemurro, L; Carberry, J; Eckert, D
Abstract: Introduction: Single-night studies with noradrenergic and anti-muscarinics have recently been shown to improve upper-airway function and reduce obstructive sleep apnoea (OSA) severity. This study aimed to determine the safety, tolerability, and efficacy profile of longer-term use of different doses of the noradrenergic agent atomoxetine combined with the anti-muscarinic oxybutynin (ato-oxy) in people with OSA. Methods: Thirty-nine people with predominantly severe OSA received either 80/5mg ato-oxy, 40/5mg ato-oxy, 40/2.5mg ato-oxy or placebo nightly for 30 days according to a double-blind, randomised, parallel design. Safety and tolerability were assessed via weekly phone calls for adverse events, vital signs and objective measures of alertness and memory. Participants completed 3 in-laboratory sleep studies (baseline, night 1 and night 30) to assess efficacy. Results: Side effects were generally mild and consistent with the known side-effect profile of each drug alone (e.g. dose-dependent increases in dry mouth with oxybutynin). Heart rate increased by night 30 in two of the drug arms versus placebo (e.g. 80/5mg ~9 beats/min, p=0.01). Blood pressure and measures of alertness and memory did not change between conditions. AHI4 and hypoxic burden decreased by ~50% in the 80/5mg arm on night 1 with similar magnitude reductions at night 30. ~50% of participants indicated willingness to continue taking the medication post-study. Discussion: 1 month of nightly noradrenergic and anti-muscarinic combination therapy is generally well-tolerated with a side effect profile consistent with each agent alone. These findings also further highlight the potential to target noradrenergic and anti-muscarinic mechanisms for OSA pharmacotherapy development.